Influence of Self-Actualization and Rewards on Employee Work Achievement at PT. Aneka Bumi Pratama Simpang Kubu Kandang Village Pemayung District - Setiawati, Neng; Wahyudi, Satya; Ningsih, Aria; Nurkodri, Moh Sahroni (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
Introduction/Main Objectives: The aim of this research is to determine the effect of selfactualization and appreciation on employee work performance at PT. Aneka Bumi Pratama, Simpang Kubu Kandang Village, Pemayung District, Batang Hari Regency. Background Problems: Self-actualization is often defined as a creative tendency that exists in a person, to achieve this can be done by recognizing one's potential in doing work that suits one's interests and is supported by talent so as to achieve success and appreciation from the company. Rewards can be given to someone if the person concerned has performance and work enthusiasm that exceeds the standard limits set by the Company. Research Method: To obtain the data needed in this research, the method used was observation, interviews and distributing questionnaires to selected respondents representing a population of 56 respondents. Multiple linear regression is the analytical tool used in this research. Findings/Results Partially, the t test of self-actualization has a positive effect on work performance. Meanwhile, awards do not show any influence on work performance. In the F test, selfactualization and appreciation simultaneously (together) influence work performance, while in the coefficient of determination test (R2 test). Conclusion: The partial t test shows that self-actualization influences the work performance of PT employees. Aneka Bumi Pratama, while awards have no influence on the work performance of PT employees. Aneka Bumi Pratama. Simultaneously (together) based on the F Test, it shows that selfactualization and appreciation influence work performance.